P-glycoprotein-mediated efflux and drug sequestration in lysosomes confer advantages of K562 multidrug resistance sublines to survive prolonged exposure to cytotoxic agents - Nathupakorn Dechsupa (2018)
Problem statement: Cellular drug resistance to anticancer agents is major obstacle in cancer chemotherapy and the mechanisms by which these MDR cells possess for protecting themselves to survive prolonged exposure to cytotoxic agents still debating. The study aimed to clarify the role of P-glycoprotein (Pgp) and enhanced drug sequestration in lysosomes to confer the multidrug resistance K562 cells with varied degree of Pgp expression. Approach: Erythromyelogenous leukemic K562 and its corresponding Pgp-over expression K562/adr (RF= 26.5) and K562/10000 (RF = 39.6) cells were used. The transport of intrinsic fluorescence molecules including acridine orange and pirarubicin across plasma membrane of living cells was performed by using spectrofluorometric and flow cytometric analysis. Results: Pirarubicin passively diffused through the plasma membrane of K562, K562/adr and K562/10000 cells with the same values of k+ = 3.4±0.3 pL. s-1.cell-1. Similar results were found for acridine orange, which passively diffused through plasma membrane of these cell lines about 30-fold faster than pirarubicin. The mean rate of Pgp-mediated efflux coefficient (ka) of pirarubicin was equal to 2.6 ± 0.9 pL.s-1.cell-1 for K562/adr and 4.7 ± 1.0 pL.s-1.cell-1 for K562/10000 cells. The Pgp-mediated efflux of acridine orange could not be determined for K562/adr cells while an enhancement of exocytosis in K562/10000 cells was characterized. The acridine orange exhibited antiproliferative activity and IC50 for K562, K562/adr and K562/10000 cells was 447±40, 715±19 and 1,719±258 nM, respectively. Cytotoxicity of acridine orange was increased by 2-fold in the presence of and 25 nM monensin. Conclusion: The results clearly demonstrated for the first time that by using the same methods and cell lines. The predominant cellular defense mechanism determined in multidrug resistant cells depends upon the nature of molecular probes used. As molecular probe, pirarubicin clearly showed that the Pgp-mediated efflux of drug play as predominant mechanism while AO clearly demonstrated the role of drug sequestration in lysosomes following an enhance exocytosis in both MDR sublines. © 2009 Science Publications.